PEMANFAATAN PLASTIK BEKAS SEBAGAI MEDIA TANAM RAMAH LINGKUNGAN DI KELURAHAN BUNGO PASANG KOTA PADANG - Nefilinda Nefilinda; Jamsari Jamsari; Elvi Zuriyani; Rika Despica; Eryka Okta Juanty; Salma Salma (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2020)
Bungo Pasang Village is one of the areas in Padang City. This area has densely populated settlements and houses with limited land. These settlements produce waste in the form of abundant organic or inorganic waste, which will impact environmental pollution. The activity objectives are to increase public knowledge and understanding of using used plastic bottles as a medium for planting flowers and environmentally friendly living pharmacies. Methods of activity: 1). lecture, 2). demonstration/training of using used plastic bottles as planting media. This activity's target audience is women in the Salingka Bungo Permai 1 Complex, Bungoasang Village, Koto Tangah District, Padang City, with about 30 members. Participants were also taught practice: punching plastic bottles, tying plastic bottles, mixing soil and fertilizer, planting flower plants in plastic bottles, and arranging plants vertically. The results of the activity obtained can increase public knowledge and awareness about using used plastic bottles as a planting medium. Furthermore, the community understands using used plastic bottles as an environmentally friendly planting medium in a little yard to the application stage of using used plastic bottles as an environmentally friendly planting medium. It is hoped that this activity can be carried out by the community in a sustainable manner to benefit people who have narrow yardlands. Furthermore, better management is needed to manage inorganic waste, such as using used bottles as planting media.